2020
DOI: 10.37190/ppmp/125266
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on energy-size distribution model of coal particle bed comminution

Abstract: In order to accurately predict the particle size distribution (PSD) of coal particle bed comminution under different applied pressures, the tests of two kinds of coal with four size fractions under five different applied pressures were carried out by TAW-3000 hydraulic servo testing machine. The Gaudin-Schumann(G-S) distribution is extended by the fractal theory and the JK size-dependent breakage model is discussed. Two mathematical models for predicting PSD of crushing products in coal particle bed comminutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…According to fractal rationale and particle extent allocation information, Zhang et al [ 22 ] constructed the fractal model of particle extent of compacted and crushed coal. Zhou et al [ 23 ] studied the crushing experiments of coal samples with two particle extents under five external pressures by using a hydraulic servo testing machine, and proposed models for predicting the particle extent allocation of coal particle crushing products. Zhang et al [ 24 ] found that the double phase fluid of gas will break great particles into granulum while it is ejected from the outburst port at high velocity, and the crushing outcome rises with the increase of methane pressure.…”
Section: Introductionmentioning
confidence: 99%
“…According to fractal rationale and particle extent allocation information, Zhang et al [ 22 ] constructed the fractal model of particle extent of compacted and crushed coal. Zhou et al [ 23 ] studied the crushing experiments of coal samples with two particle extents under five external pressures by using a hydraulic servo testing machine, and proposed models for predicting the particle extent allocation of coal particle crushing products. Zhang et al [ 24 ] found that the double phase fluid of gas will break great particles into granulum while it is ejected from the outburst port at high velocity, and the crushing outcome rises with the increase of methane pressure.…”
Section: Introductionmentioning
confidence: 99%